Characterization of a halothane-resistant strain of measles virus. - Bedows, E (1989)
A strain of measles virus (MVr) whose replication demonstrated increased resistance to halothane (2-bromo-2-chloro-1,1,1-trifluoroethane) exposure compared with the susceptible parental strain (MVs) is described. After exposure to a 1.2% halothane concentration, substantial amounts of the measles virus H protein were detected in MVr-infected Vero cell lysates by immunoprecipitation and polyacrylamide gel electrophoresis or by quantitative immunofluorescence staining. The protein was barely detectable in identically treated MVs-infected lysates, however. The recovery of all other measles virus proteins studied was the same in MVr- and MVs-infected cells at this anesthetic concentration. Thus, the altered expression of a single gene product appears to be responsible for the observed halothane resistance.